2016
DOI: 10.7202/1036104ar
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Ethics Curriculum in Canadian Initial Teacher Education

Abstract: This paper reports the results of a survey on ethics education in initial teacher education in Canada. Using an online survey and an academic calendar analysis, data was collected on ethics course requirements, perceptions about ethics content, institutional factors mediating the implementation of ethics courses, and teaching and learning objectives. Unexpectedly, the results showed that a required ethics course is as common in teacher education in Canada as it is in medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Another preventive method for reducing academic dishonesty preservice teachers would be to include a stand-alone course on academic integrity as part of a second-year undergraduate curriculum in teacher education (Maxwell et al, 2016;McCabe et al, 2012). Through this early coursework, students would review the research behind academic dishonesty, its potential effects on teacher preparation, and the consequences for engaging in academic misconduct as a student.…”
Section: Recommendationsmentioning
confidence: 99%
“…Another preventive method for reducing academic dishonesty preservice teachers would be to include a stand-alone course on academic integrity as part of a second-year undergraduate curriculum in teacher education (Maxwell et al, 2016;McCabe et al, 2012). Through this early coursework, students would review the research behind academic dishonesty, its potential effects on teacher preparation, and the consequences for engaging in academic misconduct as a student.…”
Section: Recommendationsmentioning
confidence: 99%
“…Full details of the methodology and findings can be found inMaxwell, Tremblay-Laprise, and Filion (2015) andMaxwell et al (2016). 5 Owing to the well-known methodological drawbacks of online surveys(Fowler, 2002), the results of the survey are based on a non-probabilistic sample thus limiting their generalizability to the overall population of teacher educators and teacher education programs.…”
mentioning
confidence: 99%
“…When comparing ethics education programmes of various professions, international research conducted in America has found that the teaching profession is far behind other professions such as medicine and law (Maxwell et al, 2015Maxwell & Schwimmer, 2016. According to Boon (2011), pre-service teachers lack ethical training and instruction, stating that ethics training in the field of education is far less progressive when compared to other disciplines.…”
Section: List Of Tablesmentioning
confidence: 99%
“…Teacher education programmes were more concerned with the technical skill-related aspects of teaching and neglected the ethical considerations associated with teaching (Boon & Maxwell, 2016). During the 1960s, the significance of an ethics education programme began to emerge (Maxwell et al, 2015). In 1986, a movement in the United States sought to align teacher education programmes with the trend toward ethics education in other professional circles, such as medicine and law (Maxwell & Schwimmer, 2016;Maxwell, Tremblay-Laprise, & Filion, 2015;Warnick & Silverman, 2011).…”
Section: Professional Ethics Education For Teachersmentioning
confidence: 99%